The Collected Sermons of Dietrich Bonhoeffer : Volume 2 - Bonhoeffer, Dietrich, 1906-1945 (Book collections on Project MUSE., 2017)
In his preaching, Dietrich Bonhoeffer's strong, personal faith--the foundation for everything he did--shines in the darkness of Hitler's Third Reich and in the church struggle against it. Though not overtly political, Bonhoeffer's deep concern for the developments in his world is revealed in his sermons as he seeks to draw the listener into conversation with the promises and claims of the gospel-a conversation readers today are invited to join.